Optimisation of recoverable horizontal deformation and size ratio of compacted rubberized stone mastic asphalt based on rubber and binder contents using response surface methodology - Noura, Sajjad; Sabaeei, Abdulnaser; Ismat, Gailan; Mirzapour, Sina; Muniandi, Ratnasamy; Al-Mansob, Ramez; Carter, Alan (IOP Publishing Ltd, 2022)
The use of waste materials such as rubber powder in stone mastic asphalt (SMA) has improved the structural performance to some extent, and the research on the improvement is still ongoing. Rubberised stone mastic asphalt has shown good performance in terms of resilient modulus. In this research, response surface methodology was utilised to increase the efficiency in determining the recoverable horizontal deformation and samples compaction level using optimum rubber and binder content. Thirty-one tests were performed on different binders and rubber contents, and the recoverable horizontal deformation and ratio of height to the diameter of Marshall compacted samples were recorded. The ANOVA analysis showed a low P-value with a high correlation coefficient, and the optimisation showed that adding almost 3% rubber powder to SMA could improve the compaction level and desirable recoverable deformation.